Effects of Exposure Methods to Differences in Material Analysis of Plant Tanin in Leaves of Psidium guajava L. According to UV-Vis Spectroscopic photometry From Tana Toraja South Sulawesi - Pratiwi Utami, Yuri; Imrawati, Imrawati; Songga, Elpani (Annals of Mechnikov’s Institute, 2023)
Introduction. Psidium guajava L. leaf is one of the kinds of plants that are traditionally nutritious for treating diseases, previous research stated that Psidium guajava L. has tannin compounds that are known to act as astrigenic, anti diarrhea, antibacterial, and antioxidant. The aim of this study is to determine the level of tannins produced from Psidium guajava L. leaf using two methods of extraction. Materials and methods. The object of the study Psidium guajava L. leaf. The extraction methods used were maseration and sochletation, and than detection method on the difference in the results of the analysis of the levels of tannins in Psidium guajava L. leaves by UV-Vis spectroscopic photometry and to know the amount of the tannins produced. Results & discussions. The results showed total tannin levels in the extract using the Maseration method of 3,0875 mg EAT/g and sochlettation method at 3,722 mg EAT/g. Based on the results of the calculation of the tanin levels of some extracts showed that the total tanin content produced from the extraction is higher sochletationally this is due to the presence of an influence of the temperature of extraction that can be adjusted so as not to damage the required components with the addition of the extracting temperature of the necessary components can be extracted perfectly and at the extraction sochletation occurs refrigeration which causes the components not easily decomposed. This is in line with the chemical properties of tannins that are very soluble, and will increase when dissolved in hot water, and states that phenol compounds tend to be soluble in polar solvents Conclusion. It can be concluded that the extraction uses a sochletation method that has the highest tanin content compared to the sochleteation method. Keywords: Psidium guajava L., extraction method, tannins, UV-Vis spectrophotometry